Taxane resistance in castration-resistant prostate cancer: mechanisms and therapeutic strategies - Brandon Bumbaca; Wei Li (Elsevier, 2018)
Despite its good initial response and significant survival benefit in patients with castration-resistant prostate cancer (CRPC), taxane therapy inevitably encounters drug resistance in all patients. Deep understandings of taxane resistant mechanisms can significantly facilitate the development of new therapeutic strategies to overcome taxane resistance and improve CRPC patient survival. Multiple pathways of resistance have been identified as potentially crucial areas of intervention. First, taxane resistant tumor cells typically have mutated microtubule binding sites, varying tubulin isotype expression, and upregulation of efflux transporters. These mechanisms contribute to reducing binding affinity and availability of taxanes. Second, taxane resistant tumors have increased stem cell like characteristics, indicating higher potential for further mutation in response to therapy. Third, the androgen receptor pathway is instrumental in the proliferation of CRPC and multiple hypotheses leading to this pathway reactivation have been reported. The connection of this pathway to the AKT pathway has received significant attention due to the upregulation of phosphorylated AKT in CRPC. This review highlights recent advances in elucidating taxane resistant mechanisms and summarizes potential therapeutic strategies for improved treatment of CRPC. KEY WORDS: Castration-resistant prostate cancer, Drug efflux transporters, Taxane resistance, Androgen receptor, PI3K/AKT pathway, Microtubules, Cancer stem cells, Efflux transporter